2017
DOI: 10.1051/matecconf/201710304008
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Flood Disasters: Issues Concerning Data for 2D Numerical Models

Abstract: Abstract. Flood disasters are one of the worst natural disasters and they occur almost daily. Correspondingly, city managers are nowadays increasingly investing in data collection and modelling activities. Typically, flows in pipes and channels have been modelled using a onedimensional (1D) approach. Also, if the flood flows on the ground are confined to streets and curbs, the use of 1D/1D modelling approach (a.k.a. as dual drainage concept) may be a feasible way forward. However, if the flows are two-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…However, this kind of detailed information is also (usually) more expensive and more difficult to process. Abdullah et al (2017) compared many LiDAR filtering algorithms and found that, even if producing detailed maps, none of them is fully reliable in capturing some important urban features. According to Mishra et al (2022), there are some challenges related to the representation and description of urban landscapes for atmospheric, hydrologic, and hydraulic modelling.…”
Section: Introductionmentioning
confidence: 99%
“…However, this kind of detailed information is also (usually) more expensive and more difficult to process. Abdullah et al (2017) compared many LiDAR filtering algorithms and found that, even if producing detailed maps, none of them is fully reliable in capturing some important urban features. According to Mishra et al (2022), there are some challenges related to the representation and description of urban landscapes for atmospheric, hydrologic, and hydraulic modelling.…”
Section: Introductionmentioning
confidence: 99%